ARTIFICIAL INTELLIGENCE IN ACCOUNTING: A NEW REALITY - Zarina Berdimuratova (TADQIQOTLAR, 2025)
This  article  explores  the  impact  of  artificial  intelligence  (AI)  on  modern accounting practices. The key areas of AI application in accounting, financial control, and  cash  flow  management  are  analyzed.  Special  focus  is  placed  on  automation, intelligent data analytics, and financial risk forecasting. The study substantiates the transformation  of  the  accountant’s  role  under  the  conditions  of  digital  economic development.